Design of Office Activity Information System at the Batam Center for Health Quarantine - Muhammad Avin Zulfikar Dangkeng; Sherly Agustini (Rey Media Grafika, 2024)
The rapid advancement of technology has provided convenience in various aspects of life, including the management of activity agendas within organizations or companies. The Batam Center for Health Quarantine currently manages activity agendas manually using Canva, which is inefficient in terms of time, accuracy, and data management. This manual process often leads to delays in recording and delivering information, as well as difficulties in retrieving historical agenda data of the leadership. Therefore, a web-based information system is needed to facilitate the management of leadership activity agendas more effectively, structurally, and integratively. This research aims to design and develop a Leadership Activity Agenda Information System at the Batam Center for Health Quarantine using the Waterfall method. This method consists of several stages: requirements analysis, system design, implementation, testing, and maintenance. The system is expected to improve efficiency in planning, monitoring, and managing activity agendas, enabling leaders to access information more quickly and accurately. The research results indicate that the designed information system can assist in managing leadership activity agendas more effectively compared to the previous manual method. With this system, the administration of activity agendas at the Batam Center for Health Quarantine can run more optimally, support overall organizational performance, increase transparency, and accelerate strategic decision-making processes.